Підвищення ефективності моделювання динамічних режимів нелінійних систем засобами адаптивних декомпозиційних алгоритмів - Квятковський, Богдан Олександрович (Національний університет "Львівська політехніка", 2012)
Дисертація присвячена питанням підвищення ефективності моделювання динамічних режимів нелінійних систем. Вдосконалено побудований на основі методів доповнення до мінімального та неперевищення максимального алгоритм розподілу навантаження між вузлами паралельної обчислювальної системи. Розроблено вдосконалення методу Скельбое вибору декомпозиції систем диференційних рівнянь. Розроблено метод вибору декомпозиції математичних моделей нелінійних систем, у якому враховано зменшення розміру кроку інтегрування рівнянь цих математичних моделей внаслідок нестійкості декомпозиційних методів. Ефективність вибору декомпозиції забезпечується розробленими методами оцінки рівня впливу зв’язків між змінними стану математичної моделі на стійкість декомпозиційних методів та апріорного порівняння трудомісткостей моделювання при різних декомпозиціях математичної моделі. Диссертация посвящена вопросам повышения эффективности моделирования динамических режимов нелинейных систем. Усовершенствовано построенный на основе методов дополнения к минимальному и непревышения максимального алгоритм распределения нагрузки между узлами параллельной вычислительной системы. Разработано усовершенствование метода Скельбое выбора декомпозиции систем дифференциальных уравнений. Разработан метод выбора декомпозиции математических моделей нелинейных систем, в котором учтено уменьшение размера шага интегрирования уравнений этих математических моделей в связи с неустойчивостью декомпозиционных методов. Эффективность выбора декомпозиции обеспечивается разработанными методами оценки уровня влияния связей между переменными состояния математической модели на устойчивость декомпозиционных методов и априорного сравнения трудоемкости моделирования при разных декомпозициях математической модели. The dissertation is dedicated to the problem of increasing of efficiency of non-linear systems dynamic regimes modeling. Mathematical and algorithmic support has been elaborated. Its implementation favours shortening of time expences for modeling. Algorithm of loading division between the nodes of parallel computational system for analyzing programmes of dynamic regimes by partitioning methods, created on the basis of completion to the minimum and not extending the maximum, has been improved. This in its turn enables the possibility of application of the algorithm in case of multi-rate integration of non-linear system mathematical models equations. For the sake of avoiding collisions, which are possible with an isochronous interaction of parallel computational system nodes during dynamic division of loading according to the improved algorithm, transaction of computational nodes interaction has been elaborated. Task of non-linear systems mathematical models partitioning selection on the ground of a priori evaluation of solution error which arises due to partitioning usage has been researched. As a result, the improvement of Skelboe method of differential equations systems partitioning selection has been elaborated which enables the possibility of taking into consideration the influence of dynamics of the modeling process on the solution error when partitioning is being selected and thus favours decreasing of the time cost for carrying out modeling. Scientific task of partitioning selection of non-linear systems mathematical models taking into consideration decreasing of step size of equations integration of these mathematical models due to numerical instability of partitioning methods has been solved. The elaborated criterion considers increasing of computational cost of modeling caused by such a decrease of the integration step size and lowering of computational cost reinforced by non-linear system mathematical model partitioning into sub-models of less dimension. The iteration method ensuring non-liner systems mathematical models partitioning selection on the ground of the stated criterion has been thus revealed. Efficiency of partitioning selection is provided by application of elaborated methods of evaluation of influence level of connections between state variables of mathematical models of non-linear system on numerical stability of partitioning methods and a priori comparison of modeling computational cost with different partitionings of non-linear system mathematical model. Approval of practical efficiency of the elaborated mathematical and algorithmic support has been obtained through modeling of dynamic regimes of electronic schemes.
Повышение эффективности моделирования динамических режимов нелинейных систем средствами адаптивных декомпозиционных алгоритмов
Increasing of efficiency of non-linear systems dynamic regimes modeling by means of the adaptive partitioning algorithms
Keywords: математичне моделювання; динамічний режим нелінійної системи; паралельна обчислювальна система; розподіл навантаження; декомпозиційний метод; адаптивний алгоритм; декомпозиція математичної моделі; математическое моделирование; динамический режим нелинейной системы; параллельная вычислительная система; аспределение нагрузки; декомпозиционный метод; адаптивный алгоритм; декомпозиция математической модели; mathematical modeling; dynamic regime of non-linear system; parallel computational system; loading division; partitioning method; adaptive algorithm; mathematical model partitioning